Laparoscopic Simple Prostatectomy: A Single Center Experience with A Long-Term Follow Up - Zeder, Robin; Heidler, Stefan; Alber, Thomas; Dalpiaz, Orietta (Urology Journal, 2023)
Purpose: The aim of this retrospective study is to assess the long-term outcomes and safety of laparoscopic simple prostatectomy. Material and Methods: Between 2012 and 2019 80 patients with prostates volumes ≥ 80 mL were treated with laparoscopic simple prostatectomy at our department. Uroflowmetry, post void residual volume and standardized questionnaires were assessed pre- and postoperatively. Perioperative complications were categorized using the Clavien-Dindo classification. Results: The mean specimen weight was 83 grams, and the mean operation time was 156 minutes. At a mean follow-up time of 40 months patients showed a significant improvement of Qmax (P = .002), IPSS (P < .001) and QoL (P < .001). Post void residual volumes decreased significantly. Complications occurred in 11 patients (13.8%), nine had mild (grade 1 - 2) and two had severe (grade 3b - 4a) complications. One conversion to open surgery due to massive prostatic adherence from previous abscess formation was recorded and one patient needed blood transfusion intraoperatively. Conclusion: laparoscopic simple prostatectomy is an effective and safe procedure for large volume prostate glands with a significant and stable long term symptoms improvement.